Centralization costs and benefits - Nir, Adam E. (Leadership in a changing world, 2023)
"The book brings an array of viewpoints coming from different contexts and disciplinary perspectives testifying to the benefit and drawbacks of centralized administration and control. Some of the chapters focus on particular national contexts attempting to assess the impact of centralized government in terms of benefits and limitations for national development and prosperity. Other chapters focus on the impact of centralization on specific issues such as crisis management, educational policy or public administration, discussing the extent to which centralized control may promote or undermine their effective management"--